AULDOUS HUXLEY:A VISIONARY EXPLORING THE HUMAN CONDITION - Olimjonova Malika Doniyor qizi; Kenjayeva Muxlisa Bahodirovna (TADQIQOTLAR.UZ, 2024)
Annotation: This article gives information about Aldous Huxley, a visionary writer and philosopher, explored the complexities of human nature and societal evolution. His dystopian masterpiece, "Brave New World," presented a chilling vision of a future where technology controls every aspect of life, raising questions about individuality, freedom, and the ethical implications of scientific progress. Huxley's later works delved into mysticism, spirituality, and the exploration of consciousness, reflecting his search for deeper meaning and understanding beyond the material world.